A novel nitrogen heterocycle platform-based highly selective and sensitive fluorescence chemosensor for the detection of Al3+ and its application in cell imaging. Issue 10 (12th February 2019) - Liu, Zengchen; Li, Shujing; Ge, Genwu; Li, Yanxia; Zhao, Chunxiang; Zhang, Hui; Yang, Zhiguang
Abstract : In the study, a highly selective and sensitive fluorescence sensor derived from nitrogen heterocycle was synthesized and characterized. Abstract : In the study, a highly selective and sensitive fluorescence sensor derived from nitrogen heterocycle was synthesized and characterized. By the fluorescence experiments, it was found to show a higher response toward Al 3+ than other commonly coexistent metal ions in C2 H5 OH/H2 O media (pH = 7.2). Moreover, the large binding constant (3.44 × 10 14 M −1 ) between Al 3+ and the sensor was calculated by fluorescence titration experiment. In addition, the synergistic effect mechanism due to photoinduced electron transfer (PET) and CN isomerization was deduced according to the fluorescence behavior. In addition, the fluorescence imaging in living cells was studied systemically, which exhibited high fluorescence sensing activity toward Al 3+ .